Blake and the assimilation of chaos - Gallant, Christine, 1940- (Princeton legacy library., 1978)
In all of his works Blake struggled with the question of how chaos can be assimilated into imaginative order. Blake's own answer changed in the course of his poetic career. Christine Gallant contends that during the ten year period of composition of Blake's first comprehensive epic, The Four Zoas, Blake's myth expanded from a closed, static system to an open, dynamic process. She further argues that it is only through attention to the changing pattern of Jungian archetypes in the poem that one can discern this profound change. Using the depth psychology of Jung, Professor Gallant presents a.